Environmental pedagogical aspects of nature experience trails – an international comparative study (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2019)
The development of nature experience trails is closely linked to nature trails. Over the past decades, nature trails have undergone significant changes. The German-speaking countries (Germany, Switzerland, Austria) played an important role in the development of nature experience trails. To explore the environmental pedagogical aspects of these establishments, we need to be familiar with the development process of nature experience trails, the changes in the concepts, the necessary criteria and clarify the numerous related concept (natural experience, environmental education). The study presents the environmental pedagogical aspects of nature experience trails based on German-language literature. It also delineates the results of an international research concerning the environmental pedagogical aspects, the objective of which is a comparative study on nature experience trails in Austria, Germany and Hungary with the development of an objective evaluation system.